CHINAS GLOBAL DISRUPTION myths and reality. - LO, CHI (EMERALD GROUP PUBL, 2021)
China's Global Disruption: Myths and Realityis the first book to bring world-systemic analyses of China into dialog with domestic analyses, and in so doing, to show how each can challenge or refine the assumptions of the other, ultimately showing that much of the global ""common sense"" about China is misinformed.